“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

How to enable pre-service teachers to design technological teaching and learning inclusively? – On the nature and consideration of basic needs in teacher training - Schröer, Franz; Tenberge, Claudia (PATT39 - PATT on the Edge Technology, Innovation and Education)
Theoretical approaches to the transformation towards an inclusive educational system in Germany mostly agree on the involvement of developmental tasks in subject related research (Hinz, 2011). The common understanding of inclusion as a process geared towards equal participation of all children (Booth, 2012) requires a reflexive questioning of established values, attitudes and practices in order to develop inclusive subject related research, teacher training and teaching and learning (Pech & Schomaker, 2013). Among other things, this results in consequences for the design of pre- service teacher training. To a large extent, teacher education is driven by the promotion of central competencies, interests and self-efficacy (Baumert & Kunter, 2011). It aims towards the development and realisation of inclusive interdisciplinary science and social studies (‘Sachunterricht’) in primary education (Moser, 2018). In conjunction with largely acknowledged constructivist approaches to teaching and learning (Möller, 2001), the development of personality, the consideration of basic needs (Deci & Ryan, 1993) and promotion of individual potentials are repeatedly fundamentally represented in subject related and pedagogical considerations (Feuser, 1989; GDSU, 2013). Therefore, the aforementioned constructivist approach is connected to several certain key paradigms for teaching and learning processes (e.g., Vygotskij, 1978; Posner et al., 1982; van de Pol et al., 2010). In this regard, the nature of primary school students’ basic needs have empirically not been sufficiently studied yet. Theoretical frameworks from motivational psychology (Deci & Ryan, 1993) do not explicitly address how individual needs differ and how the diversity of needs can be included in joint-learning, multi-perspective technology education classes. The research project the present paper is part of aims to develop a research-based concept for the professionalisation of pre-service teachers in a seminar course. Therefore, the promotion of the pre- service teachers’ interests and self-efficacy expectations have been assessed in a pre-post research design with a control group visiting another course not related to technology education and inclusion. The present paper describes and discusses first results of the project and will give an outlook on subsequent developmental tasks.
Keywords: Inclusion; basic needs; pre-service teacher training; interest; self-efficacy

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Evaluation of Metabolic Profiles of Patients with Anorexia Nervosa at Inpatient Admission, Short- and Long-Term Weight Regain—Descriptive and Pattern Analysis - Föcker, Manuel; Cecil, Alexander; Prehn, Cornelia; Adamski, Jerzy; Albrecht, Muriel; Adams, Frederike; Hinney, Anke; Libuda, Lars; Bühlmeier, Judith; Hebebrand, Johannes; Peters, Triinu; Antel, Jochen (Metabolites)
Acute anorexia nervosa (AN) constitutes an extreme physiological state. We aimed to detect state related metabolic alterations during inpatient admission and upon short- and long-term weight regain. In addition, we tested the hypothesis that metabolite concentrations adapt to those of healthy controls (HC) after long-term weight regain. Thirty-five female adolescents with AN and 25 female HC were recruited. Based on a targeted approach 187 metabolite concentrations were detected at inpatient admission (T0), after short-term weight recovery (T1; half of target-weight) and close to target weight (T2). Pattern hunter and time course analysis were performed. The highest number of significant differences in metabolite concentrations (N = 32) were observed between HC and T1. According to the detected main pattern, metabolite concentrations at T2 became more similar to those of HC. The course of single metabolite concentrations (e.g., glutamic acid) revealed different metabolic subtypes within the study sample. Patients with AN after short-term weight regain are in a greater “metabolic imbalance” than at starvation. After long-term weight regain, patients reach a metabolite profile similar to HC. Our results might be confounded by different metabolic subtypes of patients with AN.

Technisches Lernen inklusiv gestalten – Zur Beschaffenheit von Lernbedürfnissen im Kontext technikbezogenen Sachunterrichts - Schröer, Franz (Technikunterricht: handfest und geistreich - Der Beitrag technischer Bildung zur kulturellen Bildung - Tagungsband zur 21. Tagung der Deutschen Gesellschaft für Technische Bildung in Flensburg vom 20.-21. September 2019. Offenbach am Main)
Der Gedanke einer inklusiven Schule als einer Schule für alle Kinder ist, wenn auch aus der Perspektive von 100 Jahren Grundschule erst kürzlich durch die UN-Konvention über die Rechte von Menschen mit Behinderung (United Nations 2006) verstärkt, als an das Bildungssystem gerichtete Anforderung unbestritten. Die Didaktik des Sachunterrichts als wissenschaftliche Disziplin und als Instanz technikbezogenen Lernens in der Grundschule hat sich dem Thema Inklusion mit den Untersuchungen von Seitz (2005) und Schomaker (2000), für eine fachdidaktische Disziplin vergleichsweise früh zugewendet (Pech & Schomaker 2013, S. 341). Pech, Schomaker & Simon (2018, S. 12ff.) arbeiten jedoch an begrifflichen Unschärfen in einschlägigen Veröffentlichungen heraus, dass es in der Sachunterrichtsdidaktik bis heute keinen systematischen Diskurs darüber gibt, wie Inklusion zu verstehen, zu entwickeln und zu implementieren ist. Die allgemeinpädagogisch unter anderem von Feuser (2011, S. 89) für das Bildungssystem formulierte Entwicklungsaufgabe von der Segregation über die Integration zur Inklusion findet sich in Abhängigkeit von der Perspektive unterschiedlich definiert in der Sachunterrichts- bzw. Fachdidaktik wieder. Da bei der Definition von inklusivem Sachunterricht unterschiedliche wissenschaftliche Kontexte (z.B. sonderpädagogische, inklusionspädagogische oder allgemeindidaktische) zur Argumentation herangezogen werden, ist im Folgenden häufiger von der Rekontextualisierung von Inklusion in der Fachdidaktik die Rede. Die Berücksichtigung von Lernbedürfnissen und die Nutzung von individuellen Potenzialen stellt eine sich in der Sachunterrichtsdidaktik (u.a. Lichtblau 2014, S. 204; Simon 2014, S. 241; Pech, Schomaker & Simon 2018, 15f.) wie in der allgemeinen Pädagogik (Feuser 1989, S. 9; Schumann 2009, S. 51; Preuß 2018, S. 81) wiederholende Rekontextualisierung zur Beschreibung inklusiven Unterrichts dar. Potenzialorientierte (fach-)didaktische Überlegungen, also solche, die eine Orientierung an in Personen liegenden Defiziten auf der einen und standardisierten Normen auf der anderen Seite ablehnen und den Blick vermehrt auf die im Individuum, dem Fach oder einem Lerngegenstand liegenden Potenziale für eine gleichberechtigte und gleichwertige Partizipation aller Lernenden richten (Simon 2019, S. 114), erfahren derzeit vermehrt Aufmerksamkeit. Die Berücksichtigung individueller Lernbedürfnisse auf der anderen Seite bleibt in einschlägigen Veröffentlichungen dagegen oftmals theoretisch unreflektiert. Ausgehend davon leistet das vorgestellte Dissertationsvorhaben mit Blick auf technikbezogenes Lernen im Sachunterricht der Grundschule einen theoriebildend angelegten Beitrag zur Verbindung von erziehungswissenschaftlicher und sachunterrichtsdidaktischer Inklusionsforschung am Lerngegenstand Technik. Die Studie ist, ob der Offenheit des Forschungsfeldes bezogen auf technikbezogenen Sachunterricht im Kontext von Inklusion, überwiegend qualitativ-rekonstruktiv angelegt. Unter der Rekontextualisierung von Inklusion als Berücksichtigung zunehmend vielfältiger Lernbedürfnisse im Sachunterricht, fragt die Studie nach der Beschaffenheit und Dimensionen der Verschiedenheit von Lernbedürfnissen sowie Möglichkeiten bzw. Hindernissen auf dem Weg zu ihrer Berücksichtigung.
Keywords: Inclusion; Sachunterricht; basic needs; technology education

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Lemma „Wild/Wildnis" - Öhlschläger, Claudia (Neue Romantik. Eine kleine Literaturgeschichte 1989-2019)

Kulturtransferforschung und Musikwissenschaft - Münzmay, Andreas (Zwischen Transfer und Transformation: Horizonte der Rezeption von Musik)
Discusses the research paradigm of ‘transferts culturels’ (cultural transfers), as established by French C.N.R.S. scholars Michel Espagne and Michael Werner in the 1980s and rapidly evolving in the context of French-German research after 1989, from the point of view of musicology. Ideological categories like ‘nation’ and ‘culture’ are weighed against frames that allow for more precise definitions, like local/regional repertoires or culture politics. Likewise, the opposed theoretical concepts of ‘reception’ and ‘production’ fundamentally affect the conceptualization of the musical ‘work’ entity. Taking cultural transfers into account has helped stimulating practice-oriented views of music history that no longer consider modifications or adaptations of works only as derivatives or even misunderstandings of ‘the original’, but, to the contrary, acknowledge them as historical facts and cultural expressions in their own rights. The examples of Richard Wagner’s Die Meistersinger von Nürnberg and Eduard Hanslick’s Die moderne Oper show how this was already a controversial issue in the 19th century under the impression of the international nature of the standard (French) opera repertoire of the time. A concluding section points out the possibilities for the coverage of culture transfer processes arising from the implementation of the FRBR (Functional Requirements for Bibliographic Records) model in bibliographic authority data on the ‘work’ level. (Autor)

Amsterdamer Beiträge zur neueren Germanistik (Herausgebertätigkeit von Norbert Otto Eke von Bd. 58, 2005, bis Bd. 90, 2018)
Bd. 58: Hermann Hesse Today/Hermann Hesse heute. Hg. v. Ingo Cornils und Osman Durrani. Amsterdam – New York: Rodopi 2005. 221 S. Bd. 59: Textmaschinenkörper. Genderorientierte Lektüren des Androiden. Hg. v. Eva Kormann, Anke Gilleir und Angelika Schlimmer. Amsterdam – New York: Rodopi 2006. 253 S. Bd. 60: Bombs Away! Representing the Air War over Europe and Japan. Hg. V. Wilfried Rasch und William Rasch. Amsterdam – New York: Rodopi 2006. 404 S. Bd. 61: Schiller: National Poet – Poet of Nations. A Birmingham Symposium. Hg. v. Nicholas Martin. Amsterdam – New York: Rodopi 2006. 341 S. Bd. 62: The Enlightened Eye. Goethe and Visual Culture. Hg. v. Evelyn K. Moore und Patricia Anne Simpson. Amsterdam – New York: Rodopi 2007. 322 S. Bd. 63: Processes of Transposition. German Literature and Film. Hg. v. Christiane Schönfeld in Verbindung mit Hermann Rasche. Amsterdam – New York: Rodopi 2007. 384 S. Bd. 64: Literatur im Krebsgang. Totenbeschwörung und memoria in der deutschsprachigen Literatur nach 1989. Hg. v. Arne De Winde und Anke Gilleir. Amsterdam – New York: Rodopi 2008. 363 S. Bd. 65: Trunkenheit. Kulturen des Rausches. Hg. v. Thomas Strässle und Simon Zumsteg. Amsterdam – New York: Rodopi 2008. 266 S. Bd. 66: „Verwisch die Spuren!“ Bertolt Brecht’s Work and Legacy. A Reassess-ment. Hg. v. Robert Gillet und Godela Weiss-Sussex. Amsterdam – New York: Rodopi 2008. 359 S. Bd. 67: Neulektüren – New Readings. Festschrift für Gerd Labroisse zum 80. Geburtstag. Hg. v. Norbert Otto Eke und Gerhard P. Knapp. Amsterdam – New York: Rodopi 2009. 389 S. Bd. 68: Exiles Traveling. Exploring Displacement, Crossing Boundaries in German Exile Arts and Writing 1933-1945. Hg. v. Johannes F. Evelein. Amsterdam – New York: Rodopi 2009. 391 S. Bd. 69: Von der nationalen zur internationalen Literatur. Transkulturelle deutschsprachige Literatur und Kultur im Zeitalter globaler Migration. Hg. v. Helmut Schmitz. Amsterdam – New York: Rodopi 2009. 362 S. Bd. 70: Gender and Laughter. Comic Affirmation and Subversion in Traditional and Modern Media. Hg. v. Gaby Pailer, Andreas Böhn, Stefan Horlacher und Ulrich Scheck. Amsterdam – New York: Rodopi 2009. 386 S. Bd. 71: „Friede, Freiheit, Brot!“ Romane zur deutschen Novemberrevolution. Hg. v. Ulrich Kittstein und Regine Zeller. Amsterdam – New York: Rodopi 2009. 368 S. Bd. 72: Schreiben expatria / Expatriate Writing. Hg. von Gerhard Fischer. Amsterdam – New York: Rodopi 2009. 527 S. Bd. 73: Justitiabilität und Rechtmäßigkeit. Verrechtlichungsprozesse von Literatur und Film in der Moderne. Hg. von Claude D. Conter. Amsterdam – New York: Rodopi 2010. 286 S. Bd. 74: Wege des essayistischen Schreibens im deutschsprachigen Raum (1900-1920). Hg. von Marina Marzia Brambilla und Maurizio Pirro. Amsterdam – New York: Rodopi 2010. 442 S. Bd. 75: Spatial Turns. Space, Place, and Mobility in German Literary and Visual Culture. Hg. von Jaimey Fisher und Barbara Mennel. Amsterdam – Ney York: Rodopi 2010. 469 S. Bd. 76: Weltanschauliche Orientierungsversuche im Exil / New Orientations of World View in Exile. Hg. von Reinhard Andress. Mitherausgeber Evelyn Meyer und Greg Divers. Amsterdam – Ney York: Rodopi 2010. 371 S. Bd. 77: Karl Philipp Moritz. Signaturen des Denkens. Hg. von Anthony Krupp. Amsterdam – New York. Rodopi 2011. 314 S. Bd. 78: GeschlechterSpielRäume. Dramatik, Theater, Performance und Gender. Hg. von Gaby Pailer und Franziska Schößler. Amsterdam – New York. Rodopi 2011. 374 S. Bd. 79: Contemplating Violence. Critical Studies in Modern German Culture. Hg. von Stefani Engelstein und Carl Niekerk. Amsterdam – New York. Rodopi 2011. 296 S. Bd. 80: Deutsch-afrikanische Diskurse in Geschichte und Gegenwart. Literatur- und kulturwissenschaftliche Perspektiven. Hg. von Michael Hofmann und Rita Morrien. Amsterdam-New York: Rodopi 2012. 317 S. Bd. 81: Commitment and Compassion. Essays on Georg Büchner. Festschrift for Gerhard P. Knapp. Hg. von Patrick Fortmann und Martha B. Helfer. Amsterdam-New York: Rodopi 2012. 345 S. Bd. 82: Literatur inter- und transmedial / Inter- and Transmedial Literature. Hg. von David Bathrick und Heinz-Peter Preußer. Amsterdam-New York: Rodopi 2012. 450 S. Bd. 83: „Nach der Mauer der Abgrund“? (Wieder-)Annäherungen an die DDR-Literatur. Hg. von Norbert Otto Eke. Amsterdam-New York: Rodopi 2013. 362 S. Bd. 84: Der Nationalsozialismus und die Shoah in der deutschsprachigen Gegenwartsliteratur. Hg. von Torben Fischer, Philipp Hammermeister und Sven Kramer. Amsterdam – New York: Rodopi 2014. 344 S. Bd. 85: Voices from Exile. Essays in Memory of Hamish Ritchie. Hg. von Ian Wallace. Leiden, Boston: Brill Rodopi 2015. 337 S. Bd. 86: Scholarly Editing and German Literature. Hg. Von Lydia Jones, Bodo Plachta, Gaby Pailer und Catherine Karen Roy. Leiden, Boston: Brill Rodopi 2015. 306 S. Bd. 87: Networks of Refugees from Nazi Germany. Continuities, Reorientations, and Collaborations in Exile. Hg. von Helga Schreckenberger. Leiden, Boston: Brill Rodopi 2016. 293 S. Bd. 88: Der Essay als Universalgattung des Zeitalters. Diskurse, Themen und Positionen zwischen Jahrhundertwende und Nachkriegszeit. Hg. von Michael Ansel, Jürgen Egyptien und Hans-Edwin Friedrich. Leiden, Boston: Brill Rodopi 2016. 444 S. Bd. 89: Georg Büchner. Contemporary Perspectives. Hg. von Robert Gillet, Ernest Schonfield und Daniel Steuer. Leiden, Boston: Brill│Rodopi 2017. 384 S. Bd. 90: Shakespeare as German Author. Reception, Translation Theory, and Cultural Transfer.Hg. von John A.McCarthy. Leiden, Boston: Brill│Rodopi 2018. 245 S.

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Von der DDR in Gegenwart und Antike. Zur lyrischen Weltenreise des Uwe Kolbe - Elit, Stefan (Gedichte schreiben in Zeiten der Umbrüche: Deutsche und russische Lyrik seit 1989)

Fotografie: Ivor Grattan-Guinness 1989, in: Joseph W. Dauben/ Niccolò Guicciardini/ Albert Lewis/ Karn Hunger Parshall/ Adrian C. Rice, “Ivor Grattan-Guinness (June 23, 1941–December 12, 1914)”, Historia Mathematica 42 (2015) - Peckhaus, Volker
Pages 385–406, 396

Einleitung „John Fiske – Populäre Texte, Sprache und Alltagskultur (1989)“. - Jacke, Christoph (Texte zur Theorie des Pop.)

On black-box models of computation in cryptology - Jager, Tibor

Deutschsprachige Literatur(en) seit 1989

Deutschsprachige Literatur(en) seit 1989. Zur Einführung - Eke, Norbert Otto; Elit, Stefan (Zeitschrift für deutsche Philologie (Sonderheft "Deutschsprachige Literatur(en) seit 1989" zum Band 131))
Angaben zur Herausgeberschaft: Hg. von Norbert Otto Eke und Stefan Elit

Deutschsprachige Literatur(en) seit 1989

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

DIVIDING BY DEMANDING: OBJECT DIVISION THROUGH MARKET PROCEDURES - Haake, Claus-Jochen (International Game Theory Review)
We discuss a model, in which two agents may distribute finitely many objects among themselves. The conflict is resolved by means of a market procedure. Depending on the specifications, this procedure serves to achieve bargaining solutions such as the discrete Raiffa solution, the Kalai-Smorodinsky solution and the Perles-Maschler solution. The latter is axiomatized using the superadditivity axiom, which in the present context is readily interpreted as resolving a specific source of conflict potential.

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Equilibrium Selection in the Two-Population KMR Model - Hehenkamp, Burkhard (International Game Theory Review)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)

Planziel Vernichtung. Zwei Versuche über das Unfaßbare des Völkermords: Franz Werfels Die vierzig Tage des Musa Dagh (1933) und Edgar Hilsenraths Das Märchen vom letzten Gedanken (1989) - Eke, Norbert Otto (Deutsche Vierteljahrsschrift für Literaturwissenschaft und Geistesgeschichte)

Ernst Schröder und der Logizismus - Peckhaus, Volker (Philosophie und Logik. Frege-Kolloquien Jena 1989/1991)

Herta Müller: Reisende auf einem Bein. Berlin 1989; Der Teufel sitzt im Spiegel. Wie Wahrnehmung sich erfindet. Berlin 1991 - Eke, Norbert Otto (Halbasien. Zeitschrift für deutsche Literatur und Kultur Südosteuropas)

Tommaso Campanella: Mathematica (Hrsg. von A. Brissoni. Rom: Gangemi, 1989) - Hagengruber, Ruth Edith (Sudhoffs Archive)

Varadarajan, V.S. An Introduction to Harmonic Analysis on Semisimple Lie Groups (Cambridge University Press, 1989) - Hilgert, Joachim (JBer. DMV)

Friedrich Halm - Eke, Norbert Otto (Literatur Lexikon. Autoren und Werke deutscher Sprache. Bd. 4)

Dieter Forte - Eke, Norbert Otto (Harenbergs Lexikon der Weltliteratur. Autoren – Werke – Begriffe. Bd. 2)

Herta Müller - Eke, Norbert Otto (Harenbergs Lexikon der Weltliteratur. Autoren – Werke – Begriffe. Bd. 4)

Norbert Mecklenburg: Erzählte Provinz. Regionalismus und Moderne im Roman. Königstein/Ts. 2. Auflage. 1986 - Eke, Norbert Otto (Germanistik. Internationales Referatenorgan mit bibliographischen Hinweisen)

Projections of vector addition system reachability sets are semilinear - Kleine Büning, Hans; Lettmann, Theodor; Mayr, Ernst W. (Theoretical Computer Science)

Erstellung einer Ton-Dia-Schau zum Einsatz im schulischen Unterricht für den Kreis Lippe zum 40. Jubiläum des Art. 3 Abs. 2 Grundgesetz “Männer und Frauen sind gleichberechtigt” - Schlegel-Matthies, Kirsten

Chaos in the Market of Foreign Exchange, in: Rieder, Gessner, Peyer, Immhoff, Radermacher (eds) - Gries, Thomas

Heiner Müller. Apokalypse und Utopie - Eke, Norbert Otto

Nikolaus Lenau. Werke und Briefe. Historisch-kritische Gesamtausgabe. Bd. 5,1: Briefe 1812-1837. Teil 1: Text (Edition) - Eke, Norbert Otto; Vizkelety, András; Skrodzki, Karl Jürgen; Steinecke, Hartmut

Vom Ballhaus zum Gotteshaus, Vorgeschichte und Bau der katholischen St. Johannes-Kirche in Tübingen - Seng, Eva- Maria (Tübinger Blätter, 76. Jg.)